DETERMINAN VOLATILITAS HARGA SAHAM PADA PERUSAHAAN FOOD AND BEVERAGES : MODEL REGRESI PANEL - Rustam Efendi; Debbi Chyntia Ovami (SOSEK : Jurnal Sosial dan Ekonomi, 2021)
This study aims to examine and analyze the factors that influence stock price volatility in food and beverages companies listed on the Indonesia Stock Exchange in 2017-2020. Determination of the sample using the purposive sampling method, the sample obtained was 9 food and beverages companies in the 2017-2020 period so that 36 observation data were obtained. The data used are secondary data and the analysis technique used is multiple linear regression method by conducting a series of assumption tests to ensure the feasibility of the data. The data processing used in this study uses panel data regression with the help of Eviews 10 software. The results of this study found that firm size and earning volatility have a negative and significant effect on stock price volatility. However, leverage and dividend payout ratio have a positive and insignificant effect on stock price volatility. Meanwhile, based on the results of the simultaneous test (Test F) that all independent variables together and do not significantly affect the dependent variable